Pemanfaatan Sampah Sekam Padi dan Bungkus Rokok Sebagai Bahan Daur Ulang Kertas - Tika Mahardhika Putri; Iswanto Iswanto; Adib Suyanto (Poltekkes Kemenkes Yogyakarta, 2020)
Waste problem is a social phenomenon which must be in concern from all parties. GadingsariVillage in Sanden, Bantul Regency produces waste such as rice husk and cigarette packs. Bothtypes of waste contain cellulose which can be utilised in recycled paper production. The aim ofthis study was to utilize waste into a recycled paper and identify the tensile strength and absorptionof water on recycled paper. The study was an experiment with post test only design. Themeasurement consisted of water absorbency and pull srength of the recycled papers. The productionof recycled paper was yielded from three variations of comparison, i.e. 1:1, 1:2 and 0:1(control). The average results of the water absorption test were 56,2 mm, 67,4 mm and 95,6 mm,meanwhile the average of tensile strength test were 1,64 N/mm, 1,80 N/mm and 3,80 N/mm.Based on the testing of paper water absorption, it is known that all variations of paper conformsthe standards according to SNI 0499 in 2008, which are 50-100 mm. While testing the tensilestrength of paper in accordance with the SNI 14-6419 standard in 2001 is a variation of controlwhich is a minimum of 1,96 N/mm with a result of 3,80 N/mm. Therefore, the community is advisedto apply the production of recycled paper from rice husk and cigarette packs.